NGHIÊN CỨU ẢNH HƯỞNG CỦA HẠT NANO COBALT HOÁ TRỊ 0 LÊN HÀM LƯỢNG CHLOROPHYLL A VÀ CÁC THÔNG SỐ QUANG HỢP CỦA CÂY ĐẬU TƯƠNG Glycine max (L). MERRILL “DT96” - Lưu, Thị Tâm; Phạm, Thị Thu Hiền; Vũ, Thị Loan; Đặng, Diễm Hồng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
RESEARCH ON the effectS of ZEROVALENT COBALT NANOPARTICLE ON THE CHLOROPHYLL A CONTENT AND PHOTOSYNTHETIC PARAMETERS OF SOYBEAN Glycine max (L) MERRILL “DT96” The application of nanotechnology in agriculture is a promising way to increase crop production and yield, reduce the amount of fertilizer, increase the storage time of the productions and protect the environmental sustainability. Soybean is one of the four important crops of Vietnam’s agriculture and a source of food for humans and domestic animals. In this study, the effect of zerovalent cobalt nanoparticles with different concentrations (0; 0.17; 0.33 and 100 mg/kg seed) on chlorophyll a content and photosynthesis parameters of soybean plant Glycine max (L). Merr. DT96 which was planted in the autumn-winter crop in Xuan Hoa, Phuc Yen, Vinh Phuc were carried out. The obtained results showed that zerovalent cobalt nanoparticles had a positive effect on the photosynthetic parameters of soybean plants. At the used concentration of 0.33 mg cobalt/kg seed, the chlorophyll a content and photosynthetic parameters of soybean were the highest and there was a statistically significant difference compared with control. The chlorophyll a content tends to increase gradually and reaches the maximum value of 1.77 ± 0.05 mg/g fresh leaves after 40 days of sowing. The parameters related to chlorophyll fluorescence such as Fo (initial fluorescence), Fm (maximal fluorescence), Fv/Fm (maximal photochemical efficiency), effective quantum yield of photosystem II (FPSII), photosynthetic electron transport rate (ETR), Pn (net photosynthetic rate) of soybean seedlings which were treated by cobalt nanoparticles were higher than the control (except at the concentration of 100 mg/kg). The soybean seeds treated by cobalt nanoparticles had increased the chlorophyll a content of leaves and photosynthetic efficiency, leading to improve productivity of soybean.